The Effect of Entrepreneurial Orientation on Students’ Entrepreneurial Intention. The Role of University Support. - Weobong Victoria (KNUST, 2024)
A thesis submitted to the department of marketing and corporate strategy Kwame Nkrumah university of science and technology in partial fulfilment of the requirements for the degree of master of philosophy in business administration (strategic management and consulting)